Antioxidant activity screening of seven Indonesian herbal extract - Johan Sukweenadhi; Oeke Yunita; Finna Setiawan; KARTINI; Maya Theresa Siagian; nggreyni Pratiwi Danduru; Christina Avanti (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Sukweenadi J, Yunita O, Setiawan F, Kartini, Siagian MT, Danduru AP, Avanti C. 2020. Antioxidant Activity Screening of Seven Indonesian Herbal Extract. Biodiversitas 21: 2062-2067. Kumis kucing (Orthosiphon stamineus), pegagan (Centella asiatica), seledri (Apium graveolens), kunyit (Curcuma domestica), temulawak (Curcuma xanthorrhiza), tempuyung (Sonchus arvensis) and meniran (Phyllanthus niruri) are herbs that commonly used in the Indonesia folk medicine. The constituents that responsible for several important biological activities are phenolic and flavonoid compounds which also possess antioxidant activity. Antioxidant activity of those seven Indonesian herbal extracts was evaluated using DPPH, ABTS and FRAP methods. The extraction was done with the reflux method by using 80% ethanol as a solvent. The total phenol and total flavonoids from each herbal extract were measured using Folin–Ciocalteu reagent and spectrophotometry. Antioxidant activity results by DPPH method on O. stamineus, C. asiatica, A. graveolens, C. domestica, C. xanthorrhiza, S. arvensis, and P. niruri showed IC50 value at 132; ND; 2221; 361; 538; 1118; and 102 ppm, respectively. Results from ABTS method, showed IC50 value at 22; 1199; 169; 100; 82; 143; and 20 ppm respectively. While results from the FRAP method showed that the ethanolic extract of P. niruri at a concentration of 20 ppm possesses the strongest antioxidant activity (17.41 ppm AEAC/ppm extract). The content of total phenolic compounds are 22.50; 0.67; 2.16; 11.40; 7.80; 7.22; and 2.62% GAE, while the total flavonoid compounds were 19.88; 6.67; 4.06; 71.02; 34.62; 3.78; and 8.34% QE, respectively. It can be concluded that ethanolic extract of P. niruri and O. stamineus obtain the highest antioxidant activity based on DPPH, ABTS and FRAP method.